The spiritual quest : transcendence in myth, religion, and science - Torrance, Robert M. (Robert Mitchell), 1939- (University of California Press, 1994)
This treatise argues that the quest for the spirit is not a rare mystical experience, but a frequent expression of basic human impulses, rooted in our biological, psychological and social nature. It presents the quest in the myths and religious practices of tribal people throughout the world.